The need for a nationwide epidemiological study on the gambling disorder caused by compulsive sports betting in Nigeria: A narrative review - Chidiebere Emmanuel Okechukwu (Apollo Medicine)
There is a lack of detailed information on the epidemiology, prevention, and treatment of gambling disorder (GD) in Nigeria, a country that has the second-largest online sports gaming market in Africa. The objective of this review article was to emphasize the need for a nationwide epidemiological study on the GD caused by compulsive sports betting in Nigeria. The literature searches were carried out using the PubMed, Scopus, and Web of Science electronic databases regarding articles concerning sports betting, problem gambling, GD, and mental health in Nigeria using the following medical subject headings: Pathological Gambling AND Gamblings AND Federal Republic of Nigeria AND Social Epidemiology. A nationwide surveillance is necessary to determine the epidemiology, risk factors, and prevention and treatment measures for GD in Nigeria. To prevent negative public health consequences, sports gambling activities in Nigeria should be restricted and controlled. There is a need to set aside strict measures to control both legal and illegal online and offline sports betting activities in Nigeria. Moreover, the implementation of an effective mental health-care delivery policy to tackle gambling addiction and associated psychiatric comorbidities in Nigeria will enable efficient diagnosis and treatment of individuals with GD and improve relapse prevention. A well-funded and functional mental health-care system and research framework will facilitate effective mental health-care delivery among individuals at risk of GD and patients with GD in Nigeria. Expanding access to and use of mental health treatment services could substantially reduce the prevalence of GD and associated comorbidities in Nigeria.